Influence of Hydroxyl and Carboxyl Functionalized Multi-Walled Carbon Nanotube and Filler Loading on the Tensile Properties of Epoxy Composites - Ervina, Junaidi; Mariatti, Jaafar; Sinin, Hamdan (TransTech Publications, 2017)
In this study, three various types of fillers; pristine multi-walled carbon nanotube (MWCNT), hydroxyl functionalized multi-walled carbon nanotube (MWCNT-OH) and carboxyl functionalized multi-walled carbon nanotube (MWCNT-COOH) were used to prepare epoxy (EP) composites via ultrasonication and casting techniques. The effect of pristine MWCNT and functionalized MWCNT (MWCNT-OH and MWCNT-COOH) and fillers loading (0-1.0 vol%) on tensile properties of EP composites were investigated and compared. To identify the effectiveness of functional groups on the EP composites, the MWCNT, MWCNT-OH and MWCNT-COOH were compared through tensile testing. The addition of pristine MWCNT decreased the material’s tensile strength and modulus, while the addition of MWCNT-OH decreased the material’s tensile strength. However, among the EP composites, the 0.4 vol% MWCNT-COOH/EP composite exhibited a 12.80% increase in tensile strength (44 MPa). The tensile modulus of 0.4 vol% MWCNT-OH/EP and MWCNT-COOH/EP composites were found to be significantly higher compared to unfilled epoxy which were approximately 15.60% (2376 MPa) and 18.54% (2436 MPa) respectively. In conclusion, the MWCNT-COOH/EP composite showed slight improvement in both the tensile strength and modulus. The effect of functionalized MWCNT was supported by morphological analysis, which demonstrated an improvement in MWCNT-COOH dispersion with slightly fine agglomerates particles at 0.4 vol%.